Qualitative aspects of breathlessness in health and disease. Issue 8 (21st April 2009) - Smith, J; Albert, P; Bertella, E; Lester, J; Jack, S; Calverley, P
Abstract : Background: Patients with respiratory disease use many different expressions to describe the sensation they experience as breathlessness. Although previous analyses have identified multiple dimensions of breathlessness, there is little agreement about their number and nature. This study has applied a novel approach, principal component analysis (PCA), to understanding descriptions of breathlessness in health and disease and extracting representative components. Methods: 202 patients (asthma n = 60, chronic obstructive pulmonary disease n = 65, interstitial lung disease n = 41, idiopathic hyperventilation n = 36) and 30 healthy volunteers were studied. All subjects performed spirometry and gave binary responses to 45 descriptions recalling their experience of breathlessness at the end of exercise; patients repeated this for resting breathlessness. PCA identified response patterns in the questionnaire data and extracted discriminatory components. Component scores were calculated for each individual using the regression method. Results: PCA identified six distinct components of breathlessness on exercise, explaining 62.8% of the variance: (1) air hunger, (2) affective, (3) nociceptive, (4) regulation, (5) attention and (6) miscellaneous qualities. Rest components explaining 63.1% of variance were (1) affective, (2) air hunger, (3) nociceptive, (4) wheeze, (5) regulation and (6) miscellaneous. Components identified on exercise differed significantly between disease groups and controls and were related to percentage predicted forced vital capacity. Conclusion: This analysis suggests that air hunger is the dominant sensation during exercise, while affective distress characterises resting breathlessness in patients with a range of respiratory disorders including idiopathic hyperventilation where lung mechanics are normal. This suggests that common mechanisms operate in qualitative aspects of breathlessness.